Physiological differences at different growth stages of wheat and their effect on yield and yield attributing traits - Mishra, Chandra Nath; Tiwari, Vinod; Kumar, Amit; Kumar, Satish; Singh, Gyanendra; Singh, Gyanendra Pratap (Journal of Cereal Research, 2020)
India being the second largest wheat producer in the world provides 13% of global wheat supply. Traditional breeding approaches are limited by the low genetic variability, complexity of stress tolerance traits and yield components and the lack of efficient selection techniques under stress conditions. Although the physiological tolerance indices are not directly related to yield but their use might prove increasingly useful. Integration of physiological traits complimented with efficient breeding methodologies will drive the present research to the required wheat yields. A set of twelve wheat lines were used to study the effect of different physiological parameters on the overall yield and its component traits. Progressive increase in NDVI values was noticed during the vegetative phase and a definite decline in values was observed during milk development to ripening stages in the genotypes. In high yielding genotypes a sharp decline of NDVI values was observed from anthesis to milk development stage. This set of genotypes generally showed a slower increase in NDVI values from seedling growth stage to inflorescence emergence stage and faster decline from inflorescence stage to ripening stage. The grain filling occurs in high temperatures and genotypes showing faster utilization of green matter showed higher yield.